The Execution Of Additional Sanction In The Form Of Repair Due To Criminal Acts As An Effort To Restore The Environment Due To Environmental Crimes By Corporations - Alika Asmir; Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research entitled